2017
DOI: 10.1007/978-3-319-61902-6_5
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Variation in Expansive Subgrade Through Field Instrumentation and Geophysical Testing

Abstract: Abstract. Seasonal climatic variations in subgrade soil affect pavement responses and can reduce pavement serviceability. In addition to causing shrinkage and swelling in expansive subgrade, variations in moisture suction may alter the material properties of soil, which ultimately affect pavement performance. The current study monitored the seasonal variation of subgrade moisture content, rainfall, and pavement deformation of a section over State Highway 342, in Dallas, Texas. Moisture sensors were installed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…Finally, the time/day of the year was evaluated for assessing the effect of seasonal variation in pavement deformation. Past literature has shown that seasonal variation is one of the major causes of volumetric variation in pavement subgrade [12,13,19]. The preceeding section about change in resistivity with season authenticates that deformation is dependent upon season/time of the year.…”
Section: Development Of Initial Modelmentioning
confidence: 92%
See 3 more Smart Citations
“…Finally, the time/day of the year was evaluated for assessing the effect of seasonal variation in pavement deformation. Past literature has shown that seasonal variation is one of the major causes of volumetric variation in pavement subgrade [12,13,19]. The preceeding section about change in resistivity with season authenticates that deformation is dependent upon season/time of the year.…”
Section: Development Of Initial Modelmentioning
confidence: 92%
“…ERI, as geophysical testing was used to continuously profile the moisture variation beneath the pavement. It also allows the determination of moisture variation beneath the slope beside the pavements [12]. ERI measures the electric potential drop between two locations.…”
Section: Seasonal Moisture Variation By Resistivitymentioning
confidence: 99%
See 2 more Smart Citations
“…In geotechnical engineering practice, permeability coefficient, shear strength, and other relevant indexes describing the behavior of unsaturated soils can be obtained indirectly by using the soil-water characteristic curves [24][25][26][27][28][29][30]. According to the influence of matric suction on the cohesion and internal friction angle of unsaturated soil, many scholars used the Mohr-Coulomb strength failure criterion of saturated soil and the measured shear strength parameters of saturated soil and soil-water characteristic curve to predict the shear strength of unsaturated soil.…”
Section: Introductionmentioning
confidence: 99%